Compound heterozygous missense and intronic variants in B9D1 contribute to a recurrent Meckel syndrome pedigree - Jing, Huining; Xu, Bocheng; Wang, Hao; Liu, Shanling; Wang, He; Mai, Jingqun; Yao, Wencong; Zhang, Zhu (Frontiers in Genetics, 2025)
BackgroundMeckel syndrome (MKS) is an embryonically lethal ciliopathy with severe clinical manifestations, including defects of the central nervous system, bilateral renal cystic dysplasia, and postaxial polydactyly. B9 domain-containing 1 (B9D1, NP_056496.1) is a member of a small family of proteins associated with basal bodies and primary cilia in mammalian cells. B9D1 variants are associated with MKS and Joubert syndrome. However, to date, only a few cases have been reported.MethodsIn this study, we investigated a prenatally diagnosed recurrent MKS pedigree. Two fetuses of different sexes were conceived by nonconsanguineous parents. Systematic color Doppler ultrasound revealed same malformations in both fetuses during the second trimester, which included meningoencephalocele, Dandy-Walker malformation, and postaxial polydactyly. Trio whole exome sequencing (WES) and WES reanalysis were performed. The presence and effects of these variants were further validated using Sanger sequencing, RT-PCR, and minigene splicing assay at the DNA and RNA levels.ResultsTwo compound heterozygous variants, c.341G>T (p.R114L) and c.405-308_405-304del, were identified in both probands, each inherited from one unaffected parent. Both variants led to abnormal splicing. Specifically, the missense mutation c.341G>T caused the skipping of exon 4, whereas the novel deep-intronic variant c.405-308_405-304del created a new and strong acceptor site at c.405-294_405-293. Pathogenicity analysis indicated that both variants were pathogenic.ConclusionThis report presents a rare pedigree of recurrent MKS, in which two novel mutations in B9D1 are identified. Our findings expand the mutation spectrum of B9D1 and provide an accurate molecular diagnosis for genetic counseling.